The Effect of Employee Performance Evaluation on Public Services at the Ombudsman RI Representative Office of North Sumatra - Fiktor Menus Waruwu (JURNAL ILMIAH SOCIO SECRETUM, 2021)
Performance evaluation is an evaluative opinion on a person's character, behavior, or achievements as the basis for decisions and personnel development plans. The quality of public services is the core of a service performance. Service performance is an important point in the implementation of public services. The quality of public services is an indicator of the success of the public services provided. This study aims to determine the effect of employee performance evaluation on public services. To test the hypothesis using descriptive data and simple linear regression analysis. The population in this study were 30 respondents in which all employees started from superiors to security. The sample in this study is the total population of 30 respondents. As for the results of the research conducted, some conclusions can be drawn as follows: Performance evaluation partially affects public services, seen from the t-test shows the results of tcount < ttable (2,048 <4.462) with a significant value of 0.002 <0.05, meaning that if the performance evaluation improved, public services will also increase